Impact of Mitral Annular Dilation on Edge-to-Edge Therapy With MitraClip-XTR. (26th July 2021) - Kreidel, Felix; Zaid, Syed; Tamm, Alexander R.; Ruf, Tobias F.; Beiras-Fernandez, Andres; Reinold, Jenny; Geyer, Martin; da Rocha e Silva, Jaqueline; Schnitzler, Katharina; Michaela, Hell; Münzel, Thomas; Tang, Gilbert H.L.; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Mitral annular dilation has been shown to challenge successful edge-to-edge therapy with earlier MitraClip generations. Recently, third-generation MitraClip-XTR with extended clip arm length was introduced. We assessed the impact of annular dilation on residual mitral regurgitation (MR) after MitraClip-XTR repair and sought to identify cutoffs associated with suboptimal MR reduction. Methods: We included 107 patients (78.9±6.7 years; 40.2% female) with symptomatic severe MR (46.7% primary MR; 53.3% secondary MR) undergoing MitraClip-XTR repair. Annular dimensions were retrospectively assessed by 2-dimensional and 3-dimensional-transesophageal echocardiography including a semiautomated analysis. Impact of annular diameters and area on suboptimal reduction defined as ≥2+MR on transthoracic echocardiography at discharge was assessed and predictive cutoff values identified. Previously identified predictors of suboptimal outcome after MitraClip therapy were included in multivariable analysis. Results: Technical success was achieved in 93%, 1-year mortality was 23%. Suboptimal MR reduction was observed in 26% and associated with higher 1-year mortality (odds ratio, 4.5 [1.5–14.1]). End-systolic anteroposterior and intercommissural annular diameters, annular area and further vena-contracta width, effective regurgitant orifice area and left atrial volume were associated with suboptimal outcomes. Independent predictors of suboptimal reduction were end-systolic annular area (odds ratio, 1.36 [1.08–1.71] per cm 2 ) and vena-contracta width (odds ratio, 1.47 [1.04–2.09] per mm). On receiver operating characteristic analysis, 3-dimensional-transesophageal echocardiography end-systolic anteroposterior diameter >40.5 mm, intercommisural diameter >40.5 mm, and annular-area >12.50 cm 2 were the most predictive thresholds for suboptimal reduction. If all 3 annular measurements exceeded the determined threshold values, the risk for suboptimal reduction increased by 17-fold. Conclusions: Annular dilation was found to challenge successful edge-to-edge therapy also with extended-reach MitraClip-XTR. Our proposed thresholds for preprocedural annular dimensions may serve as guidance for improved patient selection in edge-to-edge repair.